2012
DOI: 10.1093/heapol/czs042
|View full text |Cite
|
Sign up to set email alerts
|

The effect of women's decision-making power on maternal health services uptake: evidence from Pakistan

Abstract: A large body of research has explored the links between women's decision making and their uptake of maternal health services, but the evidence so far is inconclusive. This study uses the Pakistan Social and Living Standards Measurement Survey to examine the influence of household decision making on women's uptake of maternal health services. We find that women's decision-making power has a significant positive correlation with maternal health services uptake and that influential males' decision-making power ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 27 publications
5
61
1
2
Order By: Relevance
“…Gendered roles and household power dynamics may be acting as barriers to a woman's ability to access screening. This is in line with studies in developing countries that have examined how gendered norms and values continue to influence access and utilization of sexual and reproductive health services in patriarchal settings [24,25]. Prior studies in Namibia have documented wide disparities in health care utilization that are rooted in income and health access inequalities, including in the areas of immunizations and maternal services [26,27].…”
Section: Discussionsupporting
confidence: 79%
“…Gendered roles and household power dynamics may be acting as barriers to a woman's ability to access screening. This is in line with studies in developing countries that have examined how gendered norms and values continue to influence access and utilization of sexual and reproductive health services in patriarchal settings [24,25]. Prior studies in Namibia have documented wide disparities in health care utilization that are rooted in income and health access inequalities, including in the areas of immunizations and maternal services [26,27].…”
Section: Discussionsupporting
confidence: 79%
“…The common pattern was that women's empowerment increased the uptake of ANC and postnatal services. [6][7][8] However, the influence of women's empowerment on skilled delivery care was weak in Ethiopia/ Eriteria [9] and Nairobi, Kenya [10] but significant in Nigeria. [11,12] Aside from maternal healthcare utilisation, Adhikari et al, [13] and Desai and Johnson [14] reported that women's empowerment was also a significant independent predictor of child mortality.…”
mentioning
confidence: 99%
“…AlMamun et al (2014) shows that microcredit programs to increase the income of poor women in urban areas in Malaysia contribute positively to their role in household decision making and empowerment. Education, employment and age are also found to be associated with the level of decision-making power (Jianakoplos and Bernasek 2008;Boateng et al 2014;Sinha 2012;Hou and Ma 2013). Other studies have shown that variations in family structure result in differences in household decision making (McConocha et al 1993;Razzouk et al 2007;Woolley 2003;Yusof and Duasa 2010).…”
Section: Introductionmentioning
confidence: 82%